Evaluation of the relationship between inflammation and bone turnover by sclerostin and Dickkopf-1 (DKK-1) levels in patients with SIRS - Mehmet Aşık; Uğur Altınışık; Hatice Betül Altınışık (Family Practice and Palliative Care, 2022)
Introduction: In intensive care units (ICU), patients remain bedridden for a long time. In addition, severe infections are frequently seen in ICUs. Both prolonged immobilization and serious infections are associated with bone tissue loss. The Wnt pathway has recently been focused on evaluating bone tissue loss. The Wnt pathway participates in both infections and the formation of bone tissue. Wnt pathway inhibitors sclerostin and Dickkopf-1 (DKK-1) inhibit bone formation and increase osteoclastic activity. In this study, we aimed to examine bone turnover by the Wnt inhibitors sclerostin and DKK-1 and their possible associations with inflammation in SIRS patients.Methods: We included 30 patients diagnosed with systemic inflammatory response syndrome (SIRS) in the study group and 16 in the control group. Serum sclerostin, DKK-1, white blood cell (WBC), and C-Reactive Protein (CRP) levels on the day of SIRS diagnosis (basal), the 7th, 14th, and 21stdays were evaluated in the study group, and the results were compared with the control group.Results: When the control group was compared with the basal SIRS, there was a significant elevation in both sclerostin (p=0.003) and DKK-1 (p=0.001). Statistical analysis showed significant decreases in sclerostin levels between basal and the 7th, 14th, and 21st days (p=0.033, p=0.003, p=0.002, respectively). Similarly, significant decreases in DKK-1 levels between basal and the 7th and 21st days (p=0.015, p=0.001, respectively) and an insignificant decrease on the 14th day (p=0.191) was observed. Sclerostin was positively and significantly correlated with WBC and CRP in basal and 7th-day measurements and WBC in 7th and 14th days. DKK-1 is positively and significantly correlated with WBC in basal and 7th-daymeasurements, while DKK-1 negatively correlates with CRP in basal-7th-day measurements.Conclusion: In this study, it was shown for the first time that the Wnt antagonists sclerostin and DKK-1 values are high in SIRS patients in ICU. Both biomarker levels decreased in parallel with the treatment. However, it could not be associated with disease severity and inflammatory marker levels. We believe that monitoring the change of Wnt antagonists will be useful in demonstrating bone turnover in patients with SIRS.Keywords: Dickkopf-1, Intensive care unit, Sclerostin, Systemic inflammatory response syndrome, Wnt signaling pathway, Bone turnover